Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper presents Italy's economic growth through innovation and reforms. It highlights that Italy's future competitiveness depends on the institutional and macroeconomic conditions that allow productive firms to innovate, expand, and attract inward foreign direct investment (FDI) that in turn will require the successful implementation of the authorities' full structural- and institutional-reform agenda. The IMF report focuses on the enforcement of civil and commercial claims in Italy as a key way to improve the environment for sustaining economic growth. There has been considerable interest in the possibility of introducing a comprehensive wealth tax in Italy, reflecting the public resistance to spending-only austerity.